Interest Saving In Islamic Banks: Profit Sharing, Religiosity, Product Diversity, And Moderation By Promotions - Putri, Rizky Cahyani; Ristianawati, Yuyun (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2024)
This research aims to analyze the influence of profit sharing, religiosity, and product diversity on interest in saving at Islamic banks, with promotion as a moderating variable. The population of this research is students at private Universities in Central Java, with a total of 465,584 people, according to the latest source from Central Statistics Agency Central Java. The sampling technique used random sampling with a sample size of 100 people after being measured using the Slovin approach. The analysis technique for this research uses multiple linear regression and moderated regression analysis (MRA). The data is processed using IBM SPSS 25 software. This research shows that partially profit sharing, religiosity, product diversity, and promotion positively and significantly affect interest in saving at Islamic banks. Promotion can moderate the relationship between profit sharing and religiosity on interest in saving at Islamic banks. However, promotion cannot moderate the relationship between product diversity and interest in saving at Islamic banks. This research can complement existing theories and be a reference source for further research. It can also be a source of information for Islamic banking to increase customer interest in saving through profit sharing, religiosity, and diversity of products and promotions.